Faktor-Faktor yang Mempengaruhi Cash Holding pada Perusahaan Manufaktur - Ellen Angelina Chandra; Ardiansyah (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The purpose of this study is to obtain empirical evidence whether firm size has positive impact on cash holding, whether liquidity has negative impact on cash holding, whether cash flow volatility has positive impact on cash holding, and growth opportunity has positive impact on cash holding for manufacturing companies in Indonesia. The sampling technique used was purposive sampling and Eviews 12 SV and Microsoft Excel 2010 was used for data processing. Research during the 2017-2019 period on 77 companies and then performed outliers on the data which reduces the number of companies to 63 companies. The results showed that firm size has no impact on cash holding, liquidity has no impact on cash holding, growth opportunity has no impact on cash holding, and cash flow volatility has positive impact on cash holding.